Análisis de dos fotografías ERTS como posibles indicadores de surgencia costera en la zona norte de Chile - Robles, Fernando L. E.; Ulloa, Alvaro L.; Pineda, José R. (Investigaciones Geográficas: Una mirada desde el sur, 1977)
Shades of gray were observed in two ERTS images off northern Chile coastal waters. These photographs were reproduced in band 5, combined with high-density yellow false colour (diazo) images; afterwards  they were contrasted against several physico-chemical and biological oceanographic  variables. A probable relationship was established among the shades of gray detected, and coastal upwelling of equatorial subsurface water. The significance of this correlation to fisheries-oceanography is discussed, as part of a national policy towards the use of remote sensors in the seach of natural resources.